Abordagens curriculares internacionais para educação infantil: o lugar que a criança ocupa nas relações sociais de creches e pré-escolas - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
This research aimed to analyze the repercussions of the curricular approaches of the Portuguese Modern Movement School (MEM), High Scope and Reggio Emilia in the Brazilian scientific productions, in order to understand their contributions in the reflection about the role that the child plays within the relations of which one is part of in kindergartens and preschools. To achieve this goal, we sought to identify the research axes of these scientific productions dealing with such international curriculum approaches; identify how the organization of time and space and the interaction of the teacher with the children contribute to the development of activities and verify the limits and possibilities of curricular proposals for early childhood education in Brazil. These approaches are references regarding the curriculum for early childhood education in the world, as they consider the child as an owner of rights, a historical human being and as active in the whole educational process along with the teacher and in the social environment. In Brazil, the approaches have entered the discussions of educational proposals of day care centers and preschools, but it is essential to comprehend how they are being understood of them and what are their possibilities and limits considering Brazilian reality. In account of this view, was conducted a bibliographic summarize in electronic repository banks of Brazilian scientific productions which bring these international curriculum approaches in their discussions. The data were organized in tables presenting general aspects of these productions. To a more precise understanding of the roles children play in school relations as well as the limits and possibilities of feasibility in Brazil, was selected and analyzed a scientific production that brought in its research corpus the Reggio Emilia approach, which was the approach with the largest number of productions found in the initial sum up. The discussions and analysis were realized based on the Historical-Cultural Theory, reference of this study. By this analysis it was found out that the main themes addressed in the productions are related to teacher education, time and space organization, interaction between the individuals (child-teacher-family-environment) and playing. In the analysis of the selected scientific work, it was possible to verify how aspects such as the use of pedagogical documentation and the studio space can help the construction of a quality early childhood education in the Brazilian territory. Activities involving such aspects highlight the role of children in the whole educational process. However, in the research analyzed there are present the permanence of teaching practices that contradict both the principles of the Reggio Emilia approach and the quality parameters for early childhood education, although was executed a formative intervention, which indicates that the transformations happen gradually and that it is necessary not only isolated actions, but a set of public policies to transform and consolidate them in the day-to-day of early childhood education.
Keywords: Educação Infantil; Abordagens Curriculares; Crianças; PRÁTICAS EDUCATIVAS, LINGUAGENS E TECNOLOGIAS; EDUCAÇÃO